2021
DOI: 10.1186/s13075-021-02480-4
|View full text |Cite
|
Sign up to set email alerts
|

Vision loss in patients with giant cell arteritis treated with tocilizumab

Abstract: Objectives Giant cell arteritis (GCA) may lead to vision loss. To what extent tocilizumab (TCZ) is able to prevent vision loss is unknown. The aim was to analyze the occurrence of vision loss in a large GCA cohort treated with TCZ. Methods In this observational monocentric study, GCA patients treated with TCZ between the years 2010 and 2018 were studied. Demographic, clinical, and laboratory data were analyzed. Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Case reports and observational studies of a small series of cases suggested that TCZ could be effective in both newly diagnosed and relapsing patients with GCA by finding a rapid clinical response within 1–2 months of treatment, the normalization of APR, and a decrease in the cumulative dose of prednisone [ 58 , 59 , 60 , 61 ]. However, in two multicenter retrospective open-label studies including 22 and 34 refractory or severe GCA and/or with unacceptable GC-related side effects, respectively [ 60 , 61 ], TCZ had to be withdrawn in 3 patients each, due to serious AEs (SAEs) and one death occurred in each study, all possibly drug-related ( Table 1 ) [ 12 , 13 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Treatment Of Giant Cell Arteritismentioning
confidence: 99%
“…Case reports and observational studies of a small series of cases suggested that TCZ could be effective in both newly diagnosed and relapsing patients with GCA by finding a rapid clinical response within 1–2 months of treatment, the normalization of APR, and a decrease in the cumulative dose of prednisone [ 58 , 59 , 60 , 61 ]. However, in two multicenter retrospective open-label studies including 22 and 34 refractory or severe GCA and/or with unacceptable GC-related side effects, respectively [ 60 , 61 ], TCZ had to be withdrawn in 3 patients each, due to serious AEs (SAEs) and one death occurred in each study, all possibly drug-related ( Table 1 ) [ 12 , 13 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Treatment Of Giant Cell Arteritismentioning
confidence: 99%
“…Two recent clinical studies have shown that TCZ can prevent the incidence of new visual manifestations in patients with GCA. 17 , 18 Despite these promising data, three of the patients (5%) reported by Unizony et al 17 and one (0.5%) by Amsler et al , 18 developed visual symptoms after starting TCZ. New episodes of ocular involvement were observed during treatment with TCZ in one patient (0.7%) in the GiACTA trial and another (6%) in the GUSTO trial.…”
Section: Introductionmentioning
confidence: 94%
“…Two placebo-controlled trials, one open-label trial, and several clinical observation studies have demonstrated the efficacy of TCZ in GCA patients to achieve GC-free remission. 13 19 However, the time course of patients with visual symptoms at the start of TCZ has not been documented in most previous studies. 13 , 14 , 16 …”
Section: Introductionmentioning
confidence: 98%
“…In the GIACTA study [ 57 ], 1 of 142 patients (0.7%) had AAION at the 24th week of treatment, under TCZ 162 mg every other week and prednisone 2 mg/d. In a recent review of 186 GCA patients treated with TCZ and rapid steroid tapering, two patients (1.1%) developed vision loss after TCZ initiation, one had a previous ocular attack and was still under 1 mg/kg/d of prednisone, while the other had received 3 pulses of 500 mg methylprednisolone followed by TCZ monotherapy [ 58 ]. The ocular risk for GCA one year or more after the start of corticoid therapy being approximately 1% [ 19 , 22 , 26 ], close to these preliminary observations under TCZ, no firm conclusion can be drawn to date on the ocular risk for GCA patients treated by TCZ compared to standard corticotherapy.…”
Section: Treatment Of Gca Patients With Ocular Manifestationsmentioning
confidence: 99%